A Study on educational and training development in Vietnam - Dao, Lan Thi Huong (KDI School, 2001)
Education is at the heart of development. The greatest progress in economic development and reducing poverty is made in countries that combine effective and equitable investment in education with sound economic policies. Education enables people to develop, use and extend their capacities; to lead healthier and more productive lives; and to participate in decision making and in the transformation of their lives and societies. The education and training system has developed since 1986 as a result of renovation process in Vietnam. The educational and training size has widened with educational socialization and non-state sector participation. However, during its development, there are some issues that need to be addressed. Although there is an increase in size, the effectiveness and the quality of education are still low as a result of some policy issues. The question here is how to improve the quality and effectiveness of educational and training in order to adapt to the industrialization and modernization cause in the coming years? This study will trace the process of educational and training development in Vietnam over fifty years, current situation, major policy issues and constraints, challenges of ongoing reform as well as to give some policies and recommendations for the educational and training development in Vietnam in the future.
Thesis(Master) --KDI School:Master of Public Policy,2001